Hard carbon material, preparation method thereof and battery
By introducing the first hard carbon particles of micropores and the second hard carbon cladding of pores into the hard carbon material, the problems of low sodium storage efficiency and reduced capacity caused by surface defects of the hard carbon material are solved, and efficient sodium storage and excellent rate performance are achieved.
Patent Information
- Application Number
- CN202510280091.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-11
AI Technical Summary
The surface of existing hard carbon materials has defects and cannot efficiently store sodium, resulting in a decrease in the material's capacity.
A hard carbon material is used that includes the first hard carbon particles and a second hard carbon cladding layer coated on the surface thereof. The first hard carbon particles have micropores inside, with an average pore size of 1 to 2.5 nm, and the second hard carbon coating has pores, a pore size of 0.5 to 10 nm, a porosity of 5 to 15%, and a thickness of 200 to 500 nm.
By reasonably controlling the surface defects and internal micropores of hard carbon materials, the sodium electrostatic effect is improved, the sodium storage space is increased, the capacity of the material is significantly improved, and the sodium ion migration rate on the surface of the material is optimized to ensure rate performance.
Smart Images

Figure CN119812324A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy batteries, and in particular to a hard carbon material, a preparation method thereof, and a battery. Background Art
[0002] As an important supplement to lithium-ion batteries, sodium-ion batteries have similar working mechanisms and compositions to lithium-ion batteries, and also have the advantages of abundant resources, low prices, and excellent performance. Hard carbon negative electrode materials have the advantages of abundant sources, simple preparation, high sodium storage capacity, low average working potential, and excellent cycle performance. They are the most promising sodium negative electrode materials. The surface adsorption of hard carbon, the interlayer and internal micropores of the material can provide abundant sodium storage space. Although the surface defects of the material can provide some capacity, too many surface defects will also lead to excessive side reactions and irreversible loss of Na; and the internal micropores of the material can only store sodium efficiently within the appropriate pore size range, otherwise it will lead to a significant reduction in gram capacity. Therefore, reasonable regulation of hard carbon surface defects and internal micropores can effectively improve the sodium battery efficiency and increase the sodium storage space to increase capacity. Summary of the invention
[0003] In view of this, the present invention is committed to providing a hard carbon material and a preparation method and a battery thereof, so as to solve the problem in the prior art that the hard carbon material has defects on its surface and cannot store sodium efficiently, thereby resulting in a decrease in the gram capacity of the material.
[0004] In order to solve the above-mentioned technical problems, the present invention is achieved as follows: A first aspect of the present invention provides a hard carbon material, the hard carbon material comprising a first hard carbon particle and a second hard carbon coating layer coated on the surface of the first hard carbon particle; The first hard carbon particles have micropores inside, and the average pore size of the micropores is 1-2.5 nm.
[0005] Optionally, the specific surface area of the first hard carbon particles is 2 to 10 m 2 / g; the pore volume of the first hard carbon particles is 0.01~0.6cm 3 / g; D50 of the first hard carbon particles is 2.5~7.8μm.
[0006] Optionally, the second hard carbon coating layer has pores, the pore diameter of the pores is 0.5-10 nm, the porosity of the second hard carbon coating layer is 5-15%; and the thickness of the second hard carbon coating layer is 200-500 nm.
[0007] Optionally, the D50 of the hard carbon material is 3-8 μm.
[0008] A second aspect of the present invention provides a method for preparing a hard carbon material, the method comprising the following steps: S1, placing the porous carbon source powder in a first inert atmosphere for a first carbonization treatment to obtain a carbonized material; S2, washing the carbonized material, mixing it with water, performing negative pressure treatment and filtering to obtain a first material; placing the first material in a second inert atmosphere for pressurized heating treatment to obtain first hard carbon particles; S3, mixing the liquid resin with the organic solvent to obtain a mixed solution; mixing and curing the first hard carbon particles with the mixed solution to obtain a second material; S4, crushing and granulating the second material to obtain second particles; placing the second particles in a third inert atmosphere for a second carbonization treatment.
[0009] Optionally, the porous carbon source powder comprises natural porous carbon source powder; the natural porous carbon source powder is selected from at least one of cotton powder, rice bran powder, coconut shell powder, reed stem powder, poplar powder and bamboo powder; and / or the liquid resin is selected from at least one of liquid phenolic resin, liquid epoxy resin and liquid acrylic resin; and / or the organic solvent is selected from at least one of methanol, ethanol and ethylene glycol; and / or the first inert atmosphere, the second inert atmosphere and the third inert atmosphere are each independently selected from at least one of argon, helium and nitrogen.
[0010] Optionally, the mass ratio of the carbonized material after washing and water is 10~20:1; and / or the mass concentration of the liquid resin in the mixed solution is 30~50%; and / or the mass ratio of the first hard carbon particles and the mixed solution is 1~1.5:1; and / or the D50 of the second particles is 3~8μm.
[0011] Optionally, in step S1, the conditions of the first carbonization treatment include: a carbonization temperature of 750-850°C and a carbonization time of 2-4 hours; in step S2, the washing treatment includes washing the carbonized material with an acid solution; the acid solution is selected from a hydrochloric acid aqueous solution and / or a nitric acid aqueous solution; the mass concentration of the acid in the acid solution is 20-30%; the conditions of the negative pressure treatment include: pumping the pressure to 100-150 Pa for 10-30 seconds; or, the conditions of the negative pressure treatment include: introducing an inert gas into the system to a pressure of 0.4-0. 6 standard atmospheres, maintained for 1~2h; the conditions of the pressurized heating treatment include: the pressurized pressure is 0.4~0.6MPa, the heating temperature is 750~850℃, and the treatment time is 10~30min; in step S3, the conditions of the mixing treatment include: the temperature is 150~180℃, and the time is 2~4h; the conditions of the curing treatment include: the temperature is 750~850℃, and the time is 1~2h; in step S4, the conditions of the second carbonization treatment include: the temperature is 1200~1400℃, and the time is 2~4h.
[0012] The third aspect of the present invention provides a negative electrode plate, which includes a current collector and a negative electrode material layer arranged on at least one surface of the current collector, wherein the negative electrode material layer includes the above-mentioned hard carbon material and / or the hard carbon material prepared according to the above-mentioned preparation method.
[0013] A fourth aspect of the present invention provides a battery, comprising a negative electrode plate, wherein the negative electrode plate is the negative electrode plate described above.
[0014] Through the above technical solution, the beneficial technical effects of the present invention are: (1) The hard carbon material of the present invention comprises a first hard carbon particle and a second hard carbon coating layer coated on the surface of the first hard carbon particle; wherein the first hard carbon particle has micropores inside and has good sodium storage performance, thereby greatly improving the material capacity.
[0015] (2) The present invention uses biomass materials as the carbon source base, which has abundant pores inside. The present invention first fills the pores with water through air pressure, and then places it in a high temperature and high pressure environment. The water inside the pores will quickly produce water vapor and react with the carbon around the pores to generate CO and H2 gas, thereby effectively controlling the shape and pore size of the pores. The pores generated under appropriate conditions have good sodium storage performance and greatly improve the material capacity. The present invention uses a mixed solution containing liquid resin and organic solvent to generate a hard carbon coating layer with fewer defects and abundant pores on the surface of the material, which can make up for the deficiency of side reactions caused by more defects on the surface of biomass carbon, reduce the loss of active sodium and improve the first effect. In the process of generating the coating layer, the volatilization of the organic solvent will generate abundant pores on the surface of the coating layer. In addition to storing sodium, these pores can also increase the migration rate of sodium ions on the surface of the material to ensure the rate performance.
[0016] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.
[0018] Figure 1 Shown is a schematic diagram of the hard carbon material provided by the present invention.
[0019] Description of reference numerals: 1. Inner layer of hard carbon; 2. Internal micropores; 3. Outer layer of hard carbon. DETAILED DESCRIPTION
[0020] The present invention discloses a hard carbon material and a preparation method and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments. Relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0021] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.
[0024] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.
[0025] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0026] In order to solve the problem in the prior art that the hard carbon material has defects on its surface and cannot store sodium efficiently, thereby reducing the gram capacity of the material, the present invention adopts the following technical solution: A first aspect of the present invention provides a hard carbon material, such as Figure 1 As shown, the hard carbon material includes a first hard carbon particle and a second hard carbon coating layer coated on the surface of the first hard carbon particle; The first hard carbon particles have micropores inside, and the average pore size of the micropores is 1-2.5 nm.
[0027] The hard carbon material of the present invention comprises a first hard carbon particle and a second hard carbon coating layer coated on the surface of the first hard carbon particle; wherein the first hard carbon particle has micropores inside, has good sodium storage performance, and greatly improves the material capacity.
[0028] According to the present invention, the specific surface area of the first hard carbon particles can ensure the lithium ion deintercalation speed and reduce the side reaction. The specific surface area of the first hard carbon particles can be 2-10 m 2 / g. Exemplarily, the specific surface area of the first hard carbon particles may be 2m 2 / g, 4m 2 / g, 6 m 2 / g, 8m 2 / g and 10 m 2 / g or any value within the range of values formed by any two of the above values. In the present invention, if the specific surface area of the first hard carbon particle is too large, it may cause excessive side reactions between the hard carbon and the electrolyte during the charge and discharge process, thereby causing capacity loss; if the specific surface area of the first hard carbon particle is too small, it may cause a reduction in the lithium ion deintercalation area, thereby affecting the charge and discharge rate. As a preferred embodiment, the specific surface area of the first hard carbon particle is 3~6m 2 / g.
[0029] According to the present invention, the pore volume of the first hard carbon particles can achieve the technical effect of taking into account both the capacity and the lithium ion diffusion efficiency. The pore volume of the first hard carbon particles can be 0.01-0.6 cm 3 / g. Exemplarily, the pore volume of the first hard carbon particles may be 0.01 cm 3 / g, 0.1 cm 3 / g, 0.2 cm 3 / g, 0.3 cm 3 / g, 0.4 cm 3 / g, 0.5 cm 3 / g and 0.6 cm 3 / g or any value within the range of any two of the above values. In the present invention, if the pore volume of the first hard carbon particle is too large, it may lead to increased side reactions and reduced capacity; if the pore volume of the first hard carbon particle is too small, it may lead to obstructed ion diffusion and poor electrolyte wettability, thereby affecting the lithium ion diffusion efficiency. Preferably, the pore volume of the first hard carbon particle is 0.1~0.2cm 3 / g.
[0030] According to the present invention, the D50 of the suitable first hard carbon particles can have the technical effect of ensuring the lithium ion deintercalation speed and reducing side reactions, and the D50 of the first hard carbon particles can be 2.5~7.8μm. Exemplarily, the D50 of the first hard carbon particles can be any value among 2.5μm, 3μm, 4μm, 5μm, 6μm, 7μm and 7.8μm or any value within the range of values composed of any two of the above values. In the present invention, if the D50 of the first hard carbon particles is too large, it may cause the migration distance of lithium ions in the material to increase and reduce the migration speed of lithium ions; if the D50 of the first hard carbon particles is too small, it may cause excessive side reactions between hard carbon and electrolyte during the charge and discharge process, resulting in capacity loss. Preferably, the D50 of the first hard carbon particles is 3.65~5.75μm.
[0031] According to the present invention, the second hard carbon coating layer has pores, and the pores of the second hard carbon coating layer can store sodium on the one hand, and on the other hand can increase the migration rate of sodium ions on the surface of the material to ensure the rate performance. In the present invention, the pore size can be 0.5~10nm. Exemplarily, the pore size of the pore can be any value among 0.5nm, 1nm, 2nm, 4nm, 6nm, 8nm and 10nm, or any value within the range of any two of the above values.
[0032] According to the present invention, the porosity of the second hard carbon coating layer can have the technical effect of increasing the migration speed of lithium ions in the hard carbon surface layer, and the porosity of the second hard carbon coating layer can be 5-15%. Exemplarily, the porosity of the second hard carbon coating layer can be any value among 5%, 7%, 9%, 11%, 13% and 15%, or any value within the range of any two of the above values.
[0033] According to the present invention, the thickness of the appropriate second hard carbon coating layer can have the technical effect of ensuring capacity, reducing side reactions and ensuring the migration rate of lithium ions, and the thickness of the second hard carbon coating layer can be 200~500nm. Exemplarily, the thickness of the second hard carbon coating layer can be any value among 200nm, 250nm, 300nm, 350nm, 400nm, 450nm and 500nm or any value within the range of values composed of any two of the above values. In the present invention, if the thickness of the second hard carbon coating layer is too large, the material capacity and the lithium ion migration rate may be reduced; if the thickness of the second hard carbon coating layer is too small, the protective effect of the coating layer on the inner layer may be weakened, the side reactions cannot be effectively suppressed, and the capacity decays rapidly during the cycle process. Preferably, the thickness of the second hard carbon coating layer is 250~350nm.
[0034] In the present invention, if the D50 of the hard carbon material is too large, it may increase the migration distance of lithium ions inside the material and reduce the migration speed of lithium ions; if the D50 of the hard carbon material is too small, it may cause excessive side reactions between hard carbon and electrolyte during the charge and discharge process, resulting in capacity loss. The D50 of the hard carbon material can be 3~8μm. Exemplarily, the D50 of the hard carbon material can be any value among 3μm, 4μm, 5μm, 6μm, 7μm and 8μm, or any value within the range of any two of the above values. As a preferred embodiment, the D50 of the hard carbon material is 4~6μm.
[0035] A second aspect of the present invention provides a method for preparing a hard carbon material, the method comprising the following steps: S1, placing the porous carbon source powder in a first inert atmosphere for a first carbonization treatment to obtain a carbonized material; S2, washing the carbonized material, mixing it with water, performing negative pressure treatment and filtering to obtain a first material; placing the first material in a second inert atmosphere for pressurized heating treatment to obtain first hard carbon particles; S3, mixing the liquid resin with the organic solvent to obtain a mixed solution; mixing and curing the first hard carbon particles with the mixed solution to obtain a second material; S4, crushing and granulating the second material to obtain second particles; placing the second particles in a third inert atmosphere for a second carbonization treatment.
[0036] The present invention uses biomass materials as the carbon source base, which has abundant pores inside. The present invention first fills water into the pores through air pressure, and then places it in a high temperature and high pressure environment. The water inside the pores will quickly produce water vapor and react with the carbon around the pores to generate CO and H2 gas, thereby effectively controlling the shape and pore size of the pores. The pores generated under appropriate conditions have good sodium storage performance and greatly improve the material capacity. The present invention uses a mixed solution containing a liquid resin and an organic solvent to generate a hard carbon coating layer with fewer defects and abundant pores on the surface of the material, which can make up for the deficiencies of side reactions caused by more defects on the surface of biomass charcoal, reduce the loss of active sodium and improve the first effect. In the process of generating the coating, the volatilization of the organic solvent will generate abundant pores on the surface of the coating. In addition to storing sodium, these pores can also increase the migration rate of sodium ions on the surface of the material to ensure the rate performance.
[0037] According to the present invention, the porous carbon source powder may include natural porous carbon source powder; illustratively, the natural porous carbon source powder may be selected from at least one of cotton powder, rice bran powder, coconut shell powder, reed stem powder, poplar powder and bamboo powder.
[0038] Illustratively, the liquid resin may be selected from at least one of liquid phenolic resin, liquid epoxy resin, and liquid acrylic resin.
[0039] Illustratively, the organic solvent may be selected from at least one of methanol, ethanol and ethylene glycol.
[0040] Illustratively, the first inert atmosphere, the second inert atmosphere, and the third inert atmosphere may each be independently selected from at least one of argon, helium, and nitrogen.
[0041] According to the present invention, the mass ratio of the carbonized material after washing and water can be 10~20:1; and / or, the mass concentration of the liquid resin in the mixed solution can be 30~50%; and / or, the mass ratio of the first hard carbon particles and the mixed solution can be 1~1.5:1; and / or, the D50 of the second particles can be 3~8μm.
[0042] According to the present invention, in step S1, the conditions of the first carbonization treatment may include: a carbonization temperature of 750-850°C and a carbonization time of 2-4h; in step S2, the washing treatment may include washing the carbonized material with an acid solution; the acid solution may be selected from a hydrochloric acid aqueous solution and / or a nitric acid aqueous solution; the mass concentration of the acid in the acid solution may be 20-30%.
[0043] In one embodiment of the present invention, the negative pressure treatment conditions may include: pumping the pressure to 100-150 Pa for 10-30 seconds. In another embodiment of the present invention, the negative pressure treatment conditions may include: introducing an inert gas into the system to 0.4-0.6 standard atmospheric pressure for 1-2 hours.
[0044] According to the present invention, the conditions of the pressurized heating treatment may include: the pressurized pressure is 0.4~0.6MPa, the heating temperature is 750~850℃, and the treatment time is 10~30min; in step S3, the conditions of the mixing treatment may include: the temperature is 150~180℃, and the time is 2~4h; the conditions of the curing treatment may include: the temperature is 750~850℃, and the time is 1~2h; in step S4, the conditions of the second carbonization treatment may include: the temperature is 1200~1400℃, and the time is 2~4h.
[0045] The third aspect of the present invention provides a negative electrode plate, which includes a current collector and a negative electrode material layer arranged on at least one surface of the current collector, wherein the negative electrode material layer includes the above-mentioned hard carbon material and / or the hard carbon material prepared according to the above-mentioned preparation method.
[0046] A fourth aspect of the present invention provides a battery, comprising a negative electrode plate, wherein the negative electrode plate is the negative electrode plate described above.
[0047] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources.
[0048] Example 1 (1) Preparation of hard carbon materials The coconut shell powder is placed in a first inert atmosphere for a first carbonization treatment to obtain a carbonized material, wherein the first inert atmosphere is argon, the temperature of the first carbonization treatment is 750°C, and the time is 2 hours. After the carbonized material is cooled, it is fully washed with a 20% hydrochloric acid aqueous solution, and then mixed with deionized water at a ratio of 1:15 for negative pressure treatment. The negative pressure treatment conditions are: the mixture is placed in a vacuum box and evacuated to 100Pa, and maintained for 2 hours; the material after negative pressure treatment is filtered to obtain the first material, and the first material is placed in a high-pressure reactor, argon is injected to adjust the pressure in the reactor to 0.4Mpa, and then the reactor is heated to 750°C and kept warm for 10 minutes to complete the reaction of H2O and the carbon on the inner wall of the pores to obtain the first hard carbon particles.
[0049] The solute liquid phenolic resin and the solvent ethanol are mixed to obtain a mixed solution with a mass concentration of 40%. The first hard carbon particles are added to the mixed solution to obtain a mixed material, the mass ratio of the first hard carbon particles to the mixed solution is 1.5, the mixed material is stirred at 150°C for 2 hours, and then placed at 750°C for 1 hour to obtain a second material; the second material is granulated into second particles with a D50 of 3μm; the second particles are placed in a third inert atmosphere for a second carbonization treatment; the third inert atmosphere is argon, the temperature of the second carbonization treatment is 1200°C, and the time is 2 hours to obtain the hard carbon material of this embodiment.
[0050] (2) Negative electrode preparation The hard carbon material, conductive carbon and binder (carboxymethyl cellulose CMC) of this embodiment are mixed in a mass ratio of 95:2.5:2.5, then dissolved in N-methylpyrrolidone (NMP), stirred evenly and coated on a 10 μm aluminum foil, and then dried and rolled to obtain a negative electrode sheet.
[0051] (3) Preparation of sodium ion batteries Then, the negative electrode sheet, the counter electrode sheet (metal sodium), the electrolyte (1 mol / L NaPF6, the solvent is EC:DEC=1:1) and the 12 μm PE separator are assembled into a battery.
[0052] Example 2 (1) Preparation of hard carbon materials The coconut shell powder is placed in a first inert atmosphere for a first carbonization treatment to obtain a carbonized material, wherein the first inert atmosphere is argon, the temperature of the first carbonization treatment is 850°C, and the time is 4 hours. After the carbonized material is cooled, it is fully washed with a 30% hydrochloric acid aqueous solution, and then mixed with deionized water at a ratio of 1:15 for negative pressure treatment. The negative pressure treatment conditions are: the mixture is placed in a vacuum box and evacuated to 150Pa, and maintained for 1 hour; the material after negative pressure treatment is filtered to obtain the first material, and the first material is placed in a high-pressure reactor, and argon is injected to adjust the pressure in the reactor to 0.6Mpa, and then the reactor is heated to 850°C and kept warm for 30 minutes to complete the reaction of H2O and the carbon on the inner wall of the pores to obtain the first hard carbon particles.
[0053] The solute liquid phenolic resin and the solvent ethanol are mixed to obtain a mixed solution with a mass concentration of 30%-50%. The first hard carbon particles are added to the mixed solution to obtain a mixed material, the mass ratio of the first hard carbon particles to the mixed solution is 1.5, the mixed material is stirred at 150°C for 2 hours, and then placed at 750°C for 1 hour to obtain a second material; the second material is granulated into second particles with a D50 of 3μm; the second particles are placed in a third inert atmosphere for a second carbonization treatment; the third inert atmosphere is argon, the temperature of the second carbonization treatment is 1200°C, and the time is 2 hours, to obtain the hard carbon material of this embodiment.
[0054] (2) Negative electrode preparation The preparation method of the negative electrode sheet in this embodiment is the same as that in Embodiment 1.
[0055] (3) Preparation of sodium ion batteries The preparation method of the sodium ion battery in this embodiment is the same as that in Example 1.
[0056] Example 3 (1) Preparation of hard carbon materials The coconut shell powder is placed in a first inert atmosphere for a first carbonization treatment to obtain a carbonized material, wherein the first inert atmosphere is argon, the temperature of the first carbonization treatment is 750°C, and the time is 2 hours. After the carbonized material is cooled, it is fully washed with a 20% hydrochloric acid aqueous solution, and then mixed with deionized water at a ratio of 1:15 for negative pressure treatment. The negative pressure treatment conditions are: the mixture is placed in a vacuum box and evacuated to 100Pa, and maintained for 2 hours; the material after negative pressure treatment is filtered to obtain the first material, and the first material is placed in a high-pressure reactor, argon is injected to adjust the pressure in the reactor to 0.4Mpa, and then the reactor is heated to 750°C and kept warm for 10 minutes to complete the reaction of H2O and the carbon on the inner wall of the pores to obtain the first hard carbon particles.
[0057] The solute liquid phenolic resin and the solvent ethanol are mixed to obtain a mixed solution with a mass concentration of 50%. The first hard carbon particles are added to the mixed solution to obtain a mixed material, the mass ratio of the first hard carbon particles to the mixed solution is 1, the mixed material is stirred at 150°C for 2 hours, and then placed at 850°C for 2 hours to obtain a second material; the second material is granulated into second particles with a D50 of 3μm; the second particles are placed in a third inert atmosphere for a second carbonization treatment; the third inert atmosphere is argon, the temperature of the second carbonization treatment is 1200°C, and the time is 2 hours to obtain the hard carbon material of this embodiment.
[0058] (2) Negative electrode preparation The preparation method of the negative electrode sheet in this embodiment is the same as that in Embodiment 1.
[0059] (3) Preparation of sodium ion batteries The preparation method of the sodium ion battery in this embodiment is the same as that in Example 1.
[0060] Example 4 (1) Preparation of hard carbon materials The preparation method of the hard carbon material in this embodiment is the same as that in Embodiment 1, except that the second material is granulated into second particles with a D50 of 8 μm.
[0061] (2) Negative electrode preparation The preparation method of the negative electrode sheet in this embodiment is the same as that in Embodiment 1.
[0062] (3) Preparation of sodium ion batteries The preparation method of the sodium ion battery in this embodiment is the same as that in Example 1.
[0063] Example 5 (1) Preparation of hard carbon materials The preparation method of the hard carbon material in this embodiment is the same as that in Embodiment 1, except that the coconut shell powder is replaced with bamboo powder.
[0064] (2) Negative electrode preparation The preparation method of the negative electrode sheet in this embodiment is the same as that in Embodiment 1.
[0065] (3) Preparation of sodium ion batteries The preparation method of the sodium ion battery in this embodiment is the same as that in Example 1.
[0066] Example 6 (1) Preparation of hard carbon materials The coconut shell powder is placed in a first inert atmosphere for a first carbonization treatment to obtain a carbonized material, wherein the first inert atmosphere is argon, the temperature of the first carbonization treatment is 750°C, and the time is 2 hours. After the carbonized material is cooled, it is fully washed with a 20% hydrochloric acid aqueous solution, and then mixed with deionized water at a ratio of 1:15 for negative pressure treatment. The negative pressure treatment conditions are: the mixture is placed in a vacuum box and evacuated to 500Pa, and maintained for 0.5 hours; the material after negative pressure treatment is filtered to obtain the first material, and the first material is placed in a high-pressure reactor, and argon is injected to adjust the pressure in the reactor to 0.2Mpa, and then the reactor is heated to 650°C and kept warm for 30 minutes to complete the reaction of H2O and the carbon on the inner wall of the pores to obtain the first hard carbon particles.
[0067] The solute liquid phenolic resin and the solvent ethanol are mixed to obtain a mixed solution with a mass concentration of 30%-50%. The first hard carbon particles are added to the mixed solution to obtain a mixed material, the mass ratio of the first hard carbon particles to the mixed solution is 1.5, the mixed material is stirred at 150°C for 2 hours, and then placed at 750°C for 1 hour to obtain a second material; the second material is granulated into second particles with a D50 of 3μm; the second particles are placed in a third inert atmosphere for a second carbonization treatment; the third inert atmosphere is argon, the temperature of the second carbonization treatment is 1200°C, and the time is 2 hours, to obtain the hard carbon material of this embodiment.
[0068] (2) Negative electrode preparation The preparation method of the negative electrode sheet in this embodiment is the same as that in Embodiment 1.
[0069] (3) Preparation of sodium ion batteries The preparation method of the sodium ion battery in this embodiment is the same as that in Example 1.
[0070] Example 7 (1) Preparation of hard carbon materials The coconut shell powder is placed in a first inert atmosphere for a first carbonization treatment to obtain a carbonized material, wherein the first inert atmosphere is argon, the temperature of the first carbonization treatment is 750°C, and the time is 2 hours. After the carbonized material is cooled, it is fully washed with a 20% hydrochloric acid aqueous solution, and then mixed with deionized water at a ratio of 1:15 for negative pressure treatment. The negative pressure treatment conditions are: the mixture is placed in a vacuum box and evacuated to 100Pa, and maintained for 2 hours; the material after negative pressure treatment is filtered to obtain the first material, and the first material is placed in a high-pressure reactor, argon is injected to adjust the pressure in the reactor to 0.4Mpa, and then the reactor is heated to 750°C and kept warm for 10 minutes to complete the reaction of H2O and the carbon on the inner wall of the pores to obtain the first hard carbon particles.
[0071] The solute liquid phenolic resin and the solvent ethanol are mixed to obtain a mixed solution with a mass concentration of 60%. The first hard carbon particles are added to the mixed solution to obtain a mixed material, the mass ratio of the first hard carbon particles to the mixed solution is 0.5, the mixed material is stirred at 200°C for 2 hours, and then placed at 900°C for 2 hours to obtain a second material; the second material is granulated into second particles with a D50 of 3μm; the second particles are placed in a third inert atmosphere for a second carbonization treatment; the third inert atmosphere is argon, the temperature of the second carbonization treatment is 1200°C, and the time is 2 hours, to obtain the hard carbon material of this embodiment.
[0072] (2) Negative electrode preparation The preparation method of the negative electrode sheet in this embodiment is the same as that in Embodiment 1.
[0073] (3) Preparation of sodium ion batteries The preparation method of the sodium ion battery in this embodiment is the same as that in Example 1.
[0074] Example 8 (1) Preparation of hard carbon materials The preparation method of the hard carbon material in this embodiment is the same as that in Embodiment 1, except that the second material is granulated into second particles with a D50 of 2 μm.
[0075] (2) Negative electrode preparation The preparation method of the negative electrode sheet in this embodiment is the same as that in Embodiment 1.
[0076] (3) Preparation of sodium ion batteries The preparation method of the sodium ion battery in this embodiment is the same as that in Example 1.
[0077] Example 9 (1) Preparation of hard carbon materials The preparation method of the hard carbon material in this embodiment is the same as that in Embodiment 1, except that the solute liquid phenolic resin and the solvent ethanol are mixed to obtain a mixed solution with a mass concentration of 80%.
[0078] (2) Negative electrode preparation The preparation method of the negative electrode sheet in this embodiment is the same as that in Embodiment 1.
[0079] (3) Preparation of sodium ion batteries The preparation method of the sodium ion battery in this embodiment is the same as that in Example 1.
[0080] Comparative Example 1 (1) Preparation of hard carbon materials The coconut shell powder is placed in a first inert atmosphere for a first carbonization treatment to obtain a carbonized material, wherein the first inert atmosphere is argon, the temperature of the first carbonization treatment is 750° C., and the time is 2 hours.
[0081] The solute liquid phenolic resin and the solvent ethanol are mixed to obtain a mixed solution with a mass concentration of 30%-50%. The carbonized material is added to the mixed solution to obtain a mixed material, the mass ratio of the carbonized material to the mixed solution is 1.5, the mixed material is stirred at 150°C for 2 hours, and then placed at 750°C for 1 hour to obtain a second material; the second material is granulated into second particles with a D50 of 3μm; the second particles are placed in a third inert atmosphere for a second carbonization treatment; the third inert atmosphere is argon, the temperature of the second carbonization treatment is 1200°C, and the time is 2 hours, to obtain the hard carbon material of this embodiment.
[0082] (2) Negative electrode preparation The preparation method of the negative electrode sheet in this comparative example is the same as that in Example 1.
[0083] (3) Preparation of sodium ion batteries The preparation method of the sodium ion battery in this comparative example is the same as that in Example 1.
[0084] Comparative Example 2 (1) Preparation of hard carbon materials The coconut shell powder is placed in a first inert atmosphere for a first carbonization treatment to obtain a carbonized material, wherein the first inert atmosphere is argon, the temperature of the first carbonization treatment is 750°C, and the time is 2 hours. After the carbonized material is cooled, it is fully washed with a 20% hydrochloric acid aqueous solution, and then mixed with deionized water at a ratio of 1:15 for negative pressure treatment. The negative pressure treatment conditions are: the mixture is placed in a vacuum box and evacuated to 100Pa, and maintained for 2 hours; the material after negative pressure treatment is filtered to obtain the first material, and the first material is placed in a high-pressure reactor, argon is injected to adjust the pressure in the reactor to 0.4Mpa, and then the reactor is heated to 750°C and kept warm for 10 minutes to complete the reaction of H2O and the carbon on the inner wall of the pores to obtain the first hard carbon particles.
[0085] The second material is granulated into first hard carbon particles with a D50 of 3 μm; the first hard carbon particles are placed in a third inert atmosphere for a second carbonization treatment; the third inert atmosphere is argon, the temperature of the second carbonization treatment is 1200°C, and the time is 2 h, to obtain the hard carbon material of this comparative example.
[0086] (2) Negative electrode preparation The preparation method of the negative electrode sheet in this comparative example is the same as that in Example 1.
[0087] (3) Preparation of sodium ion batteries The preparation method of the sodium ion battery in this comparative example is the same as that in Example 1.
[0088] Performance Testing (I) Performance test of the hard carbon materials prepared in Examples 1 to 9 and Comparative Examples 1 to 2. The test results are shown in Table 1 (1) Use transmission electron microscopy to test the cross-section of hard carbon materials and measure the diameter and number of closed pores within an area of 1*1μm. The average pore diameter is the average value of the diameters of all observable closed pores.
[0089] (2) Assuming the closed pores to be circular, the area of each closed pore is estimated by measuring the diameter. The proportion of internal micropores = the sum of all closed pore areas per unit area / 1 μm 2 (ii) The batteries prepared in Examples 1 to 9 and Comparative Examples 1 to 2 were subjected to charge and discharge experiments at 25±2°C with a charge and discharge voltage of 5mV to 3V, and the following properties were tested.
[0090] (1) Gram capacity: First, place the button battery in an environment of 25±2℃ for 8 hours, then discharge it at a constant current of 0.05C to 0.005V; then let it stand for 5 minutes, then charge it at a constant current of 0.05C to a voltage of 3.0V; then let it stand for 5 minutes, then discharge it at a constant current of 0.05C to 0.005V, and record the discharge capacity C0 at this time as the gram capacity; (2) Rate performance (rate capacity retention rate): First, place the battery in an environment of 25±2℃ for 0.5h, then discharge it at a constant current of 0.05C to 0.005V; then let it stand for 5min, then charge it at a constant current of 0.05C to a voltage of 3.0V; then let it stand for 5min, then discharge it at a constant current of 1C to 0.005V, and record the discharge capacity at this time as C1. The rate capacity retention rate = C1 / C0*100%. The larger the value, the better the rate performance. (3) First effect: First, place the battery in an environment of 25±2℃ for 8h, then discharge it at a constant current of 0.05C to 0.005V, and the resulting capacity is recorded as the 0.05C charging capacity; then, place it for 5min, charge it at a constant current of 0.05C to a voltage of 3.0V, and the resulting capacity is recorded as the 0.05C discharging capacity; first effect = 0.05C charging capacity / 0.05C discharging capacity*100%.
[0091] Table 1 As shown in Table 1, the preparation process parameters, hard carbon pore size, micropore ratio, and outer hard carbon thickness in Examples 1 to 5 are all within the preferred range. The reasonable internal micropore setting provides abundant sodium storage space and effectively improves the gram capacity. The outer hard carbon is relatively dense and has fewer defects. Although the capacity is slightly lower than that of the inner side, it has high stability and can inhibit the loss of active sodium during the charge and discharge process, thereby achieving the purpose of improving the initial efficiency.
[0092] It can be seen from the results of Example 1 and Example 6 that although Example 6 is improved compared to Comparative Example 1, the gram capacity is still low, so adjusting the process parameters of the pore optimization process will cause the pore size and micropore ratio to deviate from the design value. It can be seen from the results of Example 1 and Example 7 that adjusting the surface hard carbon coating process parameters makes the surface hard carbon coating layer thicker, and the capacity of this layer is lower than that of the inner hard carbon, and the power is also lower than that of the inner hard carbon. Once the thickness of the coating layer exceeds the specification, this will have an adverse effect on the gram capacity of the material, and the rate performance will also be greatly attenuated. It can be seen from the results of Example 1 and Example 8 that if the particle size of the material is too small, the specific surface area of the material will increase, and the increase in the contact interface with the electrolyte will lead to too many side reactions, resulting in loss of gram capacity and first effect. It can be seen from the results of Example 1 and Example 9 that in the outer hard carbon coating process, the ethanol ratio is too low, and there is not enough ethanol volatilization in the coating layer to generate abundant pores. In addition to reducing the proportion of surface hard carbon micropores and affecting the outer hard carbon capacity, its sodium ion migration efficiency will also be greatly weakened, which will not only increase the charge transfer impedance and affect the internal hard carbon capacity, but also greatly deteriorate the negative electrode rate performance. It can be seen from the results of Example 1 and Comparative Example 1 that in the internal pore optimization process, the material has uneven pore size and shape, and the proportion of closed pores that can efficiently store sodium is low, resulting in a waste of internal sodium storage space, resulting in a significant decrease in gram capacity. It can be seen from the results of Example 1 and Comparative Example 2 that when the outer hard carbon is removed, the more defects on the surface of the biomass hard carbon cannot be effectively protected. During the first charging film formation process, a large amount of sodium undergoes side reactions at the defects and is deposited on the surface of the material. Unlike the active sodium embedded in the material, these side reaction products cannot return to the positive electrode during the discharge process, resulting in a large amount of active sodium loss, resulting in a decrease in the first efficiency, and the gram capacity will also be reduced.
[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A hard carbon material, characterized in that: The hard carbon material comprises a first hard carbon particle and a second hard carbon coating layer coated on the surface of the first hard carbon particle; The first hard carbon particles have micropores inside, and the average pore size of the micropores is 1-2.5 nm.
2. The hard carbon material according to claim 1, characterized in that The specific surface area of the first hard carbon particles is 2 to 10 m 2 / g; The pore volume of the first hard carbon particles is 0.01-0.6 cm 3 / g; The D50 of the first hard carbon particles is 2.5-7.8 μm.
3. The hard carbon material according to claim 1, characterized in that The second hard carbon coating layer has pores, the pore diameter of the pores is 0.5-10 nm, and the porosity of the second hard carbon coating layer is 5-15%; The thickness of the second hard carbon coating layer is 200-500 nm.
4. The hard carbon material according to claim 1, characterized in that The D50 of the hard carbon material is 3-8 μm.
5. A method for preparing a hard carbon material, characterized in that: The preparation method comprises the following steps: S1, placing the porous carbon source powder in a first inert atmosphere for a first carbonization treatment to obtain a carbonized material; S2, washing the carbonized material, mixing it with water, performing negative pressure treatment and filtering to obtain a first material; placing the first material in a second inert atmosphere for pressurized heating treatment to obtain first hard carbon particles; S3, mixing the liquid resin with the organic solvent to obtain a mixed solution; mixing and curing the first hard carbon particles with the mixed solution to obtain a second material; S4, crushing and granulating the second material to obtain second particles; placing the second particles in a third inert atmosphere for a second carbonization treatment.
6. The preparation method according to claim 5, characterized in that: The porous carbon source powder comprises a natural porous carbon source powder; the natural porous carbon source powder is selected from at least one of cotton powder, rice bran powder, coconut shell powder, reed stem powder, poplar powder and bamboo powder; And / or, the liquid resin is selected from at least one of liquid phenolic resin, liquid epoxy resin and liquid acrylic resin; and / or, the organic solvent is selected from at least one of methanol, ethanol and ethylene glycol; And / or, the first inert atmosphere, the second inert atmosphere and the third inert atmosphere are each independently selected from at least one of argon, helium and nitrogen.
7. The preparation method according to claim 5, characterized in that: The mass ratio of the washed carbonized material to water is 10-20:1; And / or, the mass concentration of the liquid resin in the mixed solution is 30-50%; and / or, the mass ratio of the first hard carbon particles to the mixed solution is 1-1.5:1; And / or, the D50 of the second particles is 3-8 μm.
8. The preparation method according to claim 5, characterized in that: In step S1, the conditions of the first carbonization treatment include: a carbonization temperature of 750-850°C and a carbonization time of 2-4 hours; In step S2, the washing treatment includes washing the carbonized material with an acid solution; the acid solution is selected from a hydrochloric acid aqueous solution and / or a nitric acid aqueous solution; the mass concentration of the acid in the acid solution is 20-30%; The negative pressure treatment conditions include: pumping the pressure to 100-150 Pa for 10-30 seconds; or, the negative pressure treatment conditions include: introducing an inert gas into the system to 0.4-0.6 standard atmospheric pressure and maintaining it for 1-2 hours; The conditions of the pressurized heating treatment include: the pressurized pressure is 0.4-0.6 MPa, the heating temperature is 750-850°C, and the treatment time is 10-30 min; In step S3, the mixing treatment conditions include: temperature of 150-180°C and time of 2-4 hours; the curing treatment conditions include: temperature of 750-850°C and time of 1-2 hours; In step S4, the conditions of the second carbonization treatment include: a temperature of 1200-1400° C. and a time of 2-4 hours.
9. A negative electrode plate, characterized in that: The negative electrode plate includes a current collector and a negative electrode material layer arranged on at least one surface of the current collector, wherein the negative electrode material layer includes the hard carbon material according to any one of claims 1 to 4 and / or the hard carbon material prepared according to the preparation method according to any one of claims 5 to 8.
10. A battery, characterized in that: The battery comprises a negative electrode plate, and the negative electrode plate is the negative electrode plate according to claim 9.
Citation Information
Patent Citations
Hard carbon material for power and energy-storage battery and preparation method thereof
CN101916845A
Environment-friendly high-cycling-stability biomass hard carbon negative electrode material for sodium-ion battery and preparation method of green environment-friendly high-cycling-stability biomass hard carbon negative electrode material
CN117509609A
Preparation method of hard carbon negative electrode material for sodium ion battery and sodium ion battery
CN118125419A
Preparation method of high-first-effect nano blocky sodium ion battery negative electrode biomass hard carbon
CN118754099A
Negative electrode particle and preparing method thereof, negative electrode sheet, and energy-storage apparatus
US12080871B1
Cited By
Negative current collector, battery and electric equipment
CN121054705A